South-South Migration Implications for Social Policy and Development - Hujo, K.; Hujo, K.; Piper, N.; Piper, N. (Social Policy in a Development Context,, 2010)
This book seeks to explore the development and policy implications of South-South migration, specifically with regard to the role and challenges for social policy. It examines the linkages and impact of migration on gender and care regimes, human resource flows, remittances, poverty, and political organizations by or for migrants.